STIMULATION OF OOGENESIS IN THE MARINE SHRIMP METAPENAEUS AFFINIS BY STEROIDS - SAROJINI, R.; JAYALAKSHMI, K.; SAMBASIVARAO, S.; NAGABHUSHANAM, R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1987)
The effect of external steroids like estradiol and estrone on the morphological and histological structure of the ovaries of the marine shrimp, Metapenaeus affinis was studied. Morphological observations showed that the base control shrimp ovaries were Small, white in colour and their ovarian index was 1.48 - 0.07 In estradiol and estrone injected prawns, ovaries were fully developed green in colour and the ovarian index was significantly increased (5.90 - 086 and 424 - 0.62) when compared with base controls. Histological observations revealed that control and simultaneous control prawn ovaries showed oogonia and previtellogenic oocytes. After the administration of estradiol and estrone the previtellogenic oocytes changed to vitellogenic oocytes and had dense yolk globules The results obtained indicate that both estradiol and estrone have a stimulating effect on the ovaries on the shrimp M. affinis.